The characteristic of the superficial glycoconjugates of blood cells at thyroid adenoma and cancer. - Khiznyak O.M.; Stecleneva N.I. (Морфологія, 2007)
The analysis of superficial glycoconjugates structures on the blood cells has been done in patients with thyroid gland cancer and adenoma. The patients at the age from 35 to 50 years old was examined and divided into three groups: 1. patients with thyroid gland adenoma; 2. patients with thyroid gland cancer; 3. patients with intact thyroid gland. The blood smears were stained with alcian-blue with the purpose of visualization of superficial glycoconjugates which consist of sulfated groups and sialic acid. The membrane desialition was also performed by neuraminidase treatment to examine sulfated and sialated oligosaccharides correlation. The distribution of the histochemical- positive areas on the cell membrane has been studied with their quantitative features. The comparative analysis of the superficial glycoconjugates on the blood cells structure has been made in patients with thyroid gland adenoma and cancer, and with normal blood cells. The decrease of amount of sialated D-galactose rests has been determined in erythrocytes, granulocytes and agranulocytes surface in patients with thyroid cancer. The correlation between sulfated and sialated oligosaccharide rests as a receptors complex of the cells was also found to be altered.